2010
DOI: 10.1177/0162243909345835
|View full text |Cite
|
Sign up to set email alerts
|

Locating Scientific Citizenship: The Institutional Contexts and Cultures of Public Engagement

Abstract: In this article, we explore the institutional negotiation of public engagement in matters of science and technology. We take the example of the Science in Society dialogue program initiated by the UK’s Royal Society, but set this case within the wider experience of the public engagement activities of a range of charities, corporations, governmental departments, and scientific institutions. The novelty of the analysis lies in the linking of an account of the dialogue event and its outcomes to the values, practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 35 publications
3
58
0
1
Order By: Relevance
“…More frequent analyses of institutional contexts and arrangements should be performed as well, such as through the examination of public policy documents, and the representations of the public, local communities and the promotion of renewable energy those convey (Elcheroth et al, 2011), since those are media held by powerful actors to impose and reify representations (Andreouli & Howarth, 2012;Bickerstaff et al, 2010).…”
Section: How Social Representations Are Constructed and Transformedmentioning
confidence: 99%
“…More frequent analyses of institutional contexts and arrangements should be performed as well, such as through the examination of public policy documents, and the representations of the public, local communities and the promotion of renewable energy those convey (Elcheroth et al, 2011), since those are media held by powerful actors to impose and reify representations (Andreouli & Howarth, 2012;Bickerstaff et al, 2010).…”
Section: How Social Representations Are Constructed and Transformedmentioning
confidence: 99%
“…Both Wynne and Irwin have engaged with the U.K.'s Biotechnology and Biological Sciences Research Council as analysts and advocates (e.g., Doubleday & Wynne, 2011;Irwin, 2001Irwin, , 2006, concluding that emerging approaches to public engagement in the organization and more broadly in government represent an uneasy mix of old and new assumptions about the public and the appropriate modes of engagement. Bickerstaff et al (2010) found a similar institutional intransigence in their study of the Royal Society's public engagement activities, where they concluded that limited attempts at innovative forms of public engagement were undermined by tacit assumptions and cultural orderings of different kinds of knowledge within the organization.…”
Section: The Institutionalization Of Public Participationmentioning
confidence: 83%
“…At the time, as well as in later accounts, this report was viewed as a pivotal moment in democratic practice around science policy in the United Kingdom, setting in train the institutionalization of a more dialogic form of public engagement with science and science policy (e.g., Bickerstaff et al, 2010;Miller, 2001). This turn toward more deliberative forms of public engagement was in part a response to the public science controversies of the 1990s around BSE, the MMR vaccine, and Genetically Modified Organisms among others, which had been damaging to government credibility and legitimacy.…”
Section: The Institutionalization Of Public Participationmentioning
confidence: 99%
“…These detailed ethnographic insights into processes of organisational learning build on earlier studies of organisations of participation that have relied more heavily on document analysis (e.g., Rothstein, 2013) or on shorter periods of engagement with organisations (e.g., Bickerstaff et al, 2010;Pelling et al, 2008). This has enabled this paper to focus not only on changes in discourse, but also more tacit changes in organisational practices, assumptions and categories.…”
Section: Conclusion: Towards a Relational Spatial Account Of Organimentioning
confidence: 92%
“…While the science-policy interface has never been as clear-cut as the moniker suggests (Jasanoff & Wynne, 1998), attention has increasingly shifted towards a consideration of the role of civil society actors in influencing and intervening in these organisations, for example through protests and social movements (Stewart & Aitken, 2015), or invited deliberative public participation processes (Bickerstaff et al, 2010). With evolving demands for and modes of democratic engagement and constantly dynamic relations between science, technology and society, science policy organisations must be responsive and adaptable.…”
Section: Introductionmentioning
confidence: 99%